Faktor – Faktor Pembentuk Karakter Disiplin dan Tanggung Jawab Dalam Ekstrakurikuler Pramuka - Retno Wulan Ningrum; Erik Aditia Ismaya; Nur Fajrie (Jurnal Prakarsa Paedagogia, 2020)
This study aims to analyze the process of: 1) Formation of discipline character applied by the school in scout extracurricular activities. 2) Factors forming discipline and responsibility in scout extracurricular activities. This study used descriptive qualitative method. Data collection techniques used in this study are observation, in-depth interviews, photography and recording. Subjects studied were elementary school students of Muslimulan NU Kudus V grade in 2019/2020 school year who participated in scout extracurricular activities. The type of research used is descriptive qualitative. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results of the study note that the process of forming the character of the discipline and responsibilities of students in scouting activities is by the existence of various forms of activities that are interesting, challenging and fun. Like games, rigging, semaphores, morse, outbound, etc. Factors that shape the character of discipline and responsibility are divided into two factors. The first is internal factors; from oneself, the second external factor; from the school, family and community environment. Discipline and responsibility are two things that are mutually sustainable, so discipline can shape responsibilities and responsibilities can foster discipline.